Effects of replacing fishmeal with cottonseed protein concentrate on growth performance, blood metabolites, and the intestinal health of juvenile rainbow trout (Oncorhynchus mykiss) - Liu, Yang; Ma, Shuwei; Lv, Weihua; Shi, Honghe; Qiu, Guangwen; Chang, Hongmiao; Lu, Shaoxia; Wang, Di; Wang, Changan; Han, Shicheng; Liu, Hongbai (Frontiers in Immunology, 2022)
Cottonseed protein concentrate (CPC) is a potential non-food protein source for fishmeal replacement in fish feed. However, a high inclusion level of CPC in diets may have adverse effects on the metabolism and health of carnivorous fish. This study aimed to investigate CPC as a fishmeal alternative in the diet of rainbow trout Oncorhynchus mykiss based on growth performance, blood metabolites, and intestinal health. Five isonitrogenous (46% crude protein) and isolipidic (16% crude lipid) diets were formulated: a control diet (30% fishmeal) and four experimental diets with substitution of fishmeal by CPC at 25%, 50%, 75%, and 100%. A total of 600 fish (mean body weight 11.24g) were hand-fed the five formulated diets to apparent satiation for eight weeks. The results showed no adverse effects on growth performance when 75% dietary fishmeal was replaced by CPC. However, reduced growth and feed intake were observed in rainbow trout fed a fishmeal-free diet based on CPC (CPC100%). Changes in serum metabolites were also observed in CPC100% compared with the control group, including an increase in alanine aminotransferase (ALT), a decrease in alkaline phosphatase (ALP), alterations in free amino acids, and reductions in cholesterol metabolism. In addition, the CPC-based diet resulted in reduced intestinal trypsin, decreased villus height and width in the distal intestine, upregulated mRNA expression levels of inflammatory cytokines in the intestine, and impaired gut microbiota with reduced bacterial diversity and decreased abundance of Bacillaceae compared with the control group. The findings suggest that the optimum substitution rate of dietary fishmeal by CPC for rainbow trout should be less than 75%.